Standardization and deployment scenario of next generation NB-PLC technologies. (November 2016) - Masood, Bilal; Baig, Sobia
Abstract: Several efforts have been made in the recent decades with a goal to implement the Advanced Metering Infrastructure (AMI) in the power grid. These efforts laid foundation for the implementation of next generation Narrowband Power Line Communications (NB-PLC) technologies. In the recent past, standardization process has been completed by IEEE and ITU-T for the deployment of transceivers, based on Orthogonal Frequency Division Multiplexing (OFDM) NB-PLC. In this paper significance of NB-PLC with a focus on CENELEC band in the context of standardization and deployment is discussed. A comprehensive comparative analysis of Power Related Intelligent Metering Evolution (PRIME), G3-PLC and IEEE 1901.2 along with their routing techniques is presented. Moreover, deployment aspects and worldwide PLC research projects by academia are discussed.